Use of moss biomonitors for turbulent transport coefficient estimation for industrial emissions; Atmospheric Pollution Research; Vol. 8, iss. 5 - Ryzhakova (Rizhakova) N. K. Nadezhda Kirillovna (2017, 2017)
Title screen